"Bright Image" of the first wave Russian emigration literature - Ivan Bunin - Aghamirzayev, Alish Choban (Technium Social Sciences Journal, 2021)
The article examines the literary fate of the famous Russian writer, Nobel Prize winner Ivan Bunin, a bright face of Russian émigré literature, and his place in the first wave of Russian émigré literature. It is noted that the work of Ivan Bunin, one of the last magnates of classical Russian literature, has almost always been in the focus of literary criticism. After the collapse of the Soviet Union, especially in the post-Soviet space, the writer's work is involved in research from all sides, his works are carefully studied. The article touches upon the life and work of the writer who, after the October Revolution, went abroad, not reconciling with the new ideology. In the first years of emigration, it was emphasized that the controversy surrounding his work, as well as the critical views of proletarian critics and bourgeois literary critics, could not overshadow Bunin's work. It is noted that throughout his creative activity I. Bunin continued the traditions of classical Russian literature, enriched world literature with many priceless works. He created artistic images of his contemporaries - people of all social strata, both in pre-revolutionary Russia and in emigration. As a writer and intellectual, Bunin senses the types of people who play an important role in the destinies of Russia and the world, and represents them in his works. His prose is also distinguished by harmony, fluidity, rhythm, artistic perfection, expressive means and mysterious descriptions. Moreover, since the 1990s, a lot of research has been carried out on the turbulent life and rich creative path of the writer, but “unexplored pages” of Bunin's personality and work have remained. There are still unexplored pages of his work as a master of the word, who conquered the heights of literature and left his name in world literature.